2011
DOI: 10.1088/0031-9155/56/3/012
|View full text |Cite
|
Sign up to set email alerts
|

Renal uptake of bismuth-213 and its contribution to kidney radiation dose following administration of actinium-225-labeled antibody

Abstract: Clinical therapeutic studies using 225 Ac-labeled antibodies have begun. Of major concern is renal toxicity that may result from the three alpha-emitting progeny generated following the decay of 225 Ac. The purpose of this study was to determine the amount of 225 Ac and non-equilibrium progeny in the mouse kidney after the injection of 225 Ac-huM195 antibody and examine the dosimetric consequences. Groups of mice were sacrificed at 24, 96 and 144 h after injection with 225 Ac-huM195 antibody and kidneys excise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 32 publications
2
81
0
Order By: Relevance
“…Following intravenous injection of 225 Ac-huM195 immunoconjugates (22.2 kBq) into tumour-free mice the absorbed dose estimates were 15 Gy to the renal cortex and 23 Gy to the renal medulla. Almost 80% (18.2 Gy) of the estimated absorbed dose to the renal medulla was delivered by free 213 Bi generated by extrarenal decay of 225 Ac [23]. Therefore, the overall success of 225 Ac radioimmunotherapy is largely dependent on methods to reduce renal accumulation of the α-particle-emitting daughter nuclides 221 Fr and 213 Bi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following intravenous injection of 225 Ac-huM195 immunoconjugates (22.2 kBq) into tumour-free mice the absorbed dose estimates were 15 Gy to the renal cortex and 23 Gy to the renal medulla. Almost 80% (18.2 Gy) of the estimated absorbed dose to the renal medulla was delivered by free 213 Bi generated by extrarenal decay of 225 Ac [23]. Therefore, the overall success of 225 Ac radioimmunotherapy is largely dependent on methods to reduce renal accumulation of the α-particle-emitting daughter nuclides 221 Fr and 213 Bi.…”
Section: Discussionmentioning
confidence: 99%
“…Such short-lived radionuclides might affect the efficacy of targeted therapy, particularly after systemic administration, because the time could be too short to allow saturation of tumour targets before the majority of the activity has decayed [23]. To optimize therapeutic efficacy it has been suggested that α-emitters with substantially longer half-lives be used such as 225 Ac (t 1/2 10 days) [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4A) (50). The average absorbed dose to the kidneys was determined to be 0.77 GyÁkBq 21 , of which 60% was attributed to nonequilibrium 213 Bi excess (50).…”
Section: Controlling the Fate Of The Daughtersmentioning
confidence: 97%
“…Schwartz et al evaluated the contribution of nonequilibrium 213 Bi to kidney dose in mice via g-ray spectroscopy immediately after tissue harvest and at secular equilibrium ( Fig. 4A) (50). The average absorbed dose to the kidneys was determined to be 0.77 GyÁkBq 21 , of which 60% was attributed to nonequilibrium 213 Bi excess (50).…”
Section: Controlling the Fate Of The Daughtersmentioning
confidence: 99%